Wymogi kapitałowe związane z ryzykiem kredytowym w kontekście Nowej umowy kapitałowej, ze szczególnym uwzględnieniem banków spółdzielczych - Rosiński, Paweł (Capital requirements for credit risk under the new capital accord with focus on cooperative banks, 2006)
This article is an effort to assess the importance of implementing new capital requirements (adjusted to EU prime directive CRD and other laws) inside cooperative banks. The main attention is payd to proportionality rule recommended by CEBS Working Group, being a part of EU strategic structures. This very rule was originated and developed especially by means of co operative banks, where operational scale is undoubtly less complex. All parts that are crucial to this subject will be furthermore clearly described and rationally argumented. Additional relevant matter of this publication will be aimed directly at Basel Committee of Banking Supervision consultation papers concerning primary transformation barriers created by advanced rating methodologies. The significance of making difficult decisions whether to accept new concepts of internally assessing both client (PD) and transaction (LGD) or not, is going to be judged using small financial institutions which already have some achievements in the credit risk measurement field.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1128, s. 43-57